2003
DOI: 10.1046/j.1365-313x.2003.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Neither inverted repeat T‐DNA configurations nor arrangements of tandemly repeated transgenes are sufficient to trigger transgene silencing

Abstract: Summary Transgene expression was analysed in Arabidopsis T‐DNA transformants carrying defined numbers and arrangement of different reporter genes. All transgenes were placed under the control of the strong constitutive CaMV 35S promoter. High, stable transgene expression was observed in plants containing two copies of the β‐glucuronidase (GUS) gene, two or four copies of the green fluorescent protein (GFP) gene and two, four or six copies of the streptomycin phosphotransferase (SPT) gene. Thus, the mere presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 55 publications
3
81
0
1
Order By: Relevance
“…Alternatively, it may be envisioned that these lines have a duplicated T-DNA insertion in the respective locus so that the right border of the second insertion is oriented such that productive LUC1 fusions can be formed. Such more complex T-DNA insertion events have frequently been reported for T-DNA insertions (De Neve et al, 1997;Forsbach et al, 2003;Lechtenberg et al, 2003;Windels et al, 2003). In summary, we suggest that LucTrap-2 can be used as a gene trap vector that will allow generation of random LUC fusion proteins.…”
Section: Characterization Of a Luctrap-2 Collectionsupporting
confidence: 67%
“…Alternatively, it may be envisioned that these lines have a duplicated T-DNA insertion in the respective locus so that the right border of the second insertion is oriented such that productive LUC1 fusions can be formed. Such more complex T-DNA insertion events have frequently been reported for T-DNA insertions (De Neve et al, 1997;Forsbach et al, 2003;Lechtenberg et al, 2003;Windels et al, 2003). In summary, we suggest that LucTrap-2 can be used as a gene trap vector that will allow generation of random LUC fusion proteins.…”
Section: Characterization Of a Luctrap-2 Collectionsupporting
confidence: 67%
“…The different T-DNA vectors were used for Agrobacterium tumefaciensmediated transformation of Arabidopsis Columbia-0 and single-copy T-DNA lines were identified as described Lechtenberg et al, 2003). Integrity of the reporter gene cassettes was evaluated for plants of different generations using DNA gel blot and PCR analyses.…”
Section: Molecular-genetic Analysis Of Transgenic Plantsmentioning
confidence: 99%
“…While more recent studies indicated that position effects, inverted repeat T-DNA configurations, and arrangements of tandemly repeated transgenes may not be sufficient to trigger transgene silencing (Lechtenberg et al, 2003), there is strong evidence that expression levels of transgenes affect the frequencies of transgene silencing. It has been observed that highly expressing transgenes are often associated with high frequencies of transgene silencing (Lindbo et al, 1993;Vaucheret et al, 1998;Schubert et al, 2004).…”
Section: Introductionmentioning
confidence: 99%